The Translation to Catalan of "A esmorga", an Engaged Journey - Silvestre Llinares, Jaume (Madrygal. Revista de Estudios Gallegos, 2017)
The aim of this article is to analyse the translation to Catalan of A esmorga by the Galician author Eduardo Blanco Amor. This project came to an end in 2014 when the publishing house El gall Editor launched A esmorga. Hence, our endeavour is to contribute to the dialogue with the Galician writer from the translation and cultural studies scope. There is a growing interest in the dialogue with the author’s ouvre, as it is made clear with the A esmorga film adaption in 2014, or the translations to Asturian (1998), Italian (2006 and 2007), to French (2007) and to English (2012), and finally to Catalan (2014). Consequently, we will consider this Galcian-Catalan transferral, from an intercultural point of view, in order to highlight the challenges of the translation. Firstly, it is necessary to analyse the relationship between Blanco Amor and Catalan culture to show the relevancies of the aforementioned translation. Secondly, we will trace the words or expressions that have shown more resilience to the translation. We will mention the options given to these culturemes, so tied up to the Galician reality. Finally, we will make a brief reference to the content of the novel, which will help to link Galician and Catalan cultures. We will also explore the concept of the carnivalesque as described by M. Bakhtin. This will demonstrate the linguistic bond between Galician and Catalan cultures regarding linguistic and cultural oppression and diglossia.
Keywords: Widow of a Living Husband; Nation; Luís Seoane; Rafael Dieste; Exile.